Customer Engagement Marketing (Springer International Publishing, 2018)
This book provides a synthesis of research perspectives on customer engagement through a collection of chapters from thought leaders. It identifies cutting-edge metrics for capturing and measuring customer engagement and highlights best practices in implementing customer engagement marketing strategies. Responding to the rapidly changing business landscape where consumers are more connected, accessible, and informed than ever before, many firms are investing in customer engagement marketing. The book will appeal to academics, practitioners, consultants, and managers looking to improve customer engagement. .